Analysis Of The Failure Of Organizations For Prohibited of Chemical Weapon (OPCW) As The Organization For Disarmament On The Conflict Of Syria - Denik Iswardani Witarti; Anggun Puspitasari (The Republic of Indonesia Defense University, 2018)
This paper analyzes the failure of the Organization for Prohibited of Chemical Weapon (OPCW) in handling chemical weapon disarmament in Syria. The use of chemical weapons by the Syrian government against its own citizens poses a challenge for OPCW in its role to ban the use and development of chemical weapons worldwide. OPCW itself formed in 1997 is an implementation of Chemical Weapon Convention (CWC) in 1993. The main problem of this study is OPCW failure factors to ban the use and development of chemical weapons in Syrian conflict. The study results show that the chemical weapon disarmament efforts in Syria by the OPCW by sending and destroying government-owned chemical weapons has failed. Although OPCW has claimed Syria has been freed from chemical weapons, it is still encountered the use of chemical weapons by ISIS terrorist groups and unofficial opposition groups. In conclusion, the role of the OPCW according to the concept of disarmament and the international organization is still not fully successful. OPCW is only able to detect the use of chemical weapons committed by the Syrian government. This organization has no authority in overcoming the problem of the misused chemical weapons committed by non-state actors.Keywords: Chemical weapons, Syrian conflict, OPCW, Disarmament.